2018
DOI: 10.3389/fphys.2018.00795
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Systematic Review and Meta-Analysis of Astragaloside IV for Myocardial Ischemia/Reperfusion Injury

Abstract: Astragaloside IV (AS-IV), the major pharmacological extract from Astragalus membranaceus Bunge, possesses a variety of biological activities in the cardiovascular systems. Here, we aimed to evaluate preclinical evidence and possible mechanism of AS-IV for animal models of myocardial ischemia/reperfusion (I/R) injury. Studies of AS-IV in animal models with myocardial I/R injury were identified from 6 databases from inception to May, 2018. The methodological quality was assessed by using CAMARADES 10-item checkl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
(109 reference statements)
0
19
0
Order By: Relevance
“…In addition, AS/IV could reduce the number of apoptotic cardiomyocytes with H/R [30]. A meta-analysis showed AS/IV significantly reduced myocardial infarction area and protected heart function in mice compared to the control group [31]. Another similar report also indicated that AS/IV could improve myocardial H/R in rats by suppressing calcium-sensing receptormediated apoptotic signaling pathways [32].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, AS/IV could reduce the number of apoptotic cardiomyocytes with H/R [30]. A meta-analysis showed AS/IV significantly reduced myocardial infarction area and protected heart function in mice compared to the control group [31]. Another similar report also indicated that AS/IV could improve myocardial H/R in rats by suppressing calcium-sensing receptormediated apoptotic signaling pathways [32].…”
Section: Discussionmentioning
confidence: 98%
“…AS-IV increases the production of nitric oxide (NO) by activating the PI3K/Akt pathway in H9C2 cells and inactivating glycogen synthase kinase 3b (GSK-3b) through the NO/cGMP/PKG signalling pathway to prevent the mitochondrial permeability transition pore (mPTP) from opening and reperfusion injury and reduce myocardial injury [43]. AS-IV has many cardiovascular protective effects, including anti-inflammation, anti-virus, anti-oxidation, inhibition of intracellular calcium overload and foam cell formation, and protection of endothelial cells [4]. In addition, it has protective effects on diabetic nephropathy by inhibiting activation of the MEK1/2-ERK1/2-RSK2 signalling pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…AS-IV has been reported to show antioxidative stress properties, and to affect immune modulation, including anti-viral and anti-inflammatory effects [1][2][3]. AS-IV has various mechanisms to protect the myocardium, including an antioxidant and free radical removal function [4]. Astragalus has a detoxification and muscle regeneration role in the treatment of long-term muscle ulcers, indicating that astragalus functions as a scavenger in tissue and organ repair and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the efficacy and mechanisms of PGC in fatigue animal models have not been systematically evaluated yet. Systematic review of animal researches is indispensable in the process of drug development and elucidation of the physiological and pathological mechanisms (Zheng et al, 2018). Preclinical research is the key to convert preclinical data into clinical data.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%